The Significance of Professional Development for School Librarians and Teachers in Preventing Violence against Children in the Digital Environment - Sijamija, Anida Dudić; Silajdžić, Lamija; Adilović, Emina (DESIDOC Journal of Library & Information Technology, 2025)
Children and youth have predominantly shifted social activities into the digital sphere, leading to the consistent prevalence of digital technologies in the classroom. Besides numerous benefits, it also brought challenges, such as (cyber)bullying. Many teachers may approach the issue of cyberbullying with reservations, either because they do not view it as a serious problem or believe that they should not play a role in its resolution. Therefore, it is crucial to provide teachers and librarians with professional development on the challenges and risks of cyberbullying among pupils. Using quantitative method, this paper examines the competencies and experiences of teachers and librarians in Bosnia and Herzegovina in addressing the issue of cyberbullying among pupils. The importance of ongoing professional development and the availability of education in recognising risky behaviours of pupils online is particularly emphasised. The data indicates that, despite their engagement in lifelong learning, teachers and librarians require systematic and continuous training to understand and respond promptly to emerging digital risks involving children.